Defining God in the book of genesis and experiencing the absolute - Paradowski, Ryszard (Hybris, 2013)
The paper presents the philosophical interpretation of the Biblical story on anthropogenesis, contained in the introductory chapters of the Book of Genesis. The interpretation is developed on the base of the suggestion got out from „Plato's dilemma” and author's concept of metaphysics. The opinion about the relationship between philosophy and religion and the complex structure of the notion of „god” and the contents of the „mystic experience” is given.